The Political Framework of Economic Decision-making in Indonesia and Vietnam, 1945-1950 - Pham Van Thuy (Universitas Gadjah Mada, 2013)
This article identifes similarities and differences in economic institutions and in decision-making in Indonesia and Vietnam immediately after independence. It focuses on political and educational backgrounds of the economic leadership in the two nations that played an important part in explaining difference in thinking with respect to economic policies and priorities in the struggle against colonial forces. Indonesian leaders were mostly pragmatic nationalist politicians who possessed experience from management of the economy and who were inclined to adopt a liberal approach to economic policy. Economic development and national sovereignty were given higher priority in comparison to the objectives of economic nationalism. By contrast, most members of the Vietnamese government were revolutionary leaders adhering to Communist ideology. They considered the task of economic nationalism and resistance against foreign aggressors inseparable.